Under the spotlight: students' viewpoint of an oral presentation course during Open and Distant Learning (ODL) / Nor Afifa Nordin … [et al.] - Nordin, Nor Afifa; Zabidin, Nursyafiqah; Hoo, Fang Jing; Ibrahim, Raihan; Kamaludin, Puteri Nur Hidayah (Akademi Pengajian Bahasa, 2021)
The Covid-19 pandemic has caused drastic changes to be made in sustaining teaching and learning where technology-enhanced learning and open and distance learning (ODL) have to be adopted as social and physical contacts are now limited globally to mitigate the transmissions of viruses. At the same time, courses at tertiary level incorporate oral presentation as a common form of assessment. Nevertheless, students' level of performances in oral presentations is still considered unsatisfactory. Contributing factors could be students' presentations relied on content memorisation and lack of confidence in public speaking. Therefore, teaching effective presentation skills is deemed necessary in improving students' oral presentations. This study sought to discover students’ expectations and perceptions on a presentation course in ODL. The study adopted a qualitative approach, where a semi-structured interview was conducted among ten diploma students undertaking a presentation skills course in Universiti Teknologi MARA. The data gathered was descriptively analysed. The findings revealed that the course met the participants' expectations of a presentation course. Participants also claimed to face no difficulties in understanding the course content; although some participants addressed that the course should be more effective in the physical classroom due to technological issues faced. In terms of the content delivery, participants attributed instructor’s delivery of content positively, despite technological difficulties faced by several participants. Suggestions that were expressed by participants are procured to bring new insight for educators and policy makers to improve the content and pedagogies of oral presentation courses.